KADAR Na, K, Cl PADA RAGAM (VARIASI) SELANG WAKTU PEMERIKSAAN SERUM - Trisna Yustiani, Nyoman; Mutmainnah, Mutmainnah; DN Pakasi, Ruland; Hardjoeno, Hardjoeno (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2009)
The role of electrolytes in the human body is very important. Almost all metabolic processes are affected by electrolytes. The accuracyof examination results depend on the management in pre-analytical, analytical, and post-analytical processes. The management ofspecimen is one of the essential factors in pre-analytical process that may influence the accuracy of laboratory results. This study haspurposed to observe the influence of time-interval variation at the examination of Na, K, and Cl serum concentration. A cross-sectionalstudy was conducted on 30 outpatient’s serum samples who visited the Clinical Pathology Laboratory of Dr. Wahidin Sudirohusodohospital in Makassar during July to August 2007. The Na, K, and Cl serum samples were examined immediately, 1 hour-delayed, and2 hours-delayed. Data were analyzed using paired T test in SPSS version 11.5. In this study we found that there was no significantdifference for Na and Cl between immediate and delayed samples, similarly showed for K between immediate and 1 hour-delayed (p >0.05). A significant different for K between immediate and 2 hours delayed, and between the first hour and the second hour delayedsamples (p < 0.05). From this study we could conclude that delayed samples more than 2 hours had no influence for Na and Clexamination result. Delayed samples more than 2 hours for K had influence for the examination result.